Coping strategies after heart transplantation: psychological implications - Pfeifer,Paula Moraes (2013)
OBJECTIVES: To investigate coping strategies used by patients submitted to heart transplantation and whether they are related to the perception of the disease and transplantation. METHODS: Cross-sectional study with quantitative and qualitative analysis. The sample of 32 patients was assessed by the Ways of Coping Scale and socio-demographic questionnaire, and five of them were selected for interviews. The internal consistency of the scale was assessed, the variables and strategies involved were crossed and content analysis of interviews, investigating the existence of a relationship with the speech of the participants. RESULTS: The individuals have used all coping styles, with a predominance of the problem-focused strategy. Psychologically prepared patients showed a statistically significant increase in the use of problem-focused coping and seek for social support. However, a significant increase in the use of emotion-focused coping was observed in patients who were not prepared. Analysis through the method of Bardin showed as categories: disease; reaction to call; transplantation; fantasies; postoperative; team and coping. CONCLUSION: Patients with a transplanted heart make use of all coping strategies, with a predominance of the problem-focused strategy. Psychologically prepared individuals used more active coping strategies, which highlights the importance of psychological support during the process.